3‐3: Distinguished Paper: All Inkjet‐printed RGB Cd‐free EL‐QD Devices with Top‐emission Structure. Issue 1 (28th June 2022) - Park, Myoungjin; Kim, Young Il; Kang, Jin-goo; Kim, Sehun; Ha, Jaekook; Yoon, Yeo-geon; Lee, Changhee
Abstract : We demonstrated the world first all inkjet‐printed Cd‐free ELQDs based on getting over the hurdles of all inkjet printing process. Especially, we fabricated EL‐QD devices by stacking 4‐soluble layers without intermixing and have studied the factors affecting QD efficiency, QD printing and the influence of ETL solvent on QD.